Acoplamento de férmions com o campo gravitacional e aplicação na cosmologia - Barboza, Lauziene Nazareth (2018)
The proposal of this work is to present a review on the coupling of the Dirac field (fermions) to the gravitational field through the formalism of the tetrads. More specifically, an application will be made to the Friedmann-Robertson-Walker model in which the fermionic field is considered as one of the components of the cosmological fluid. A relevant consequence is the possibility that fermions are candidates for dark energy content by replacing the standard approach with the cosmological constant.